A Study of the Fluorescence Properties of 1,8-Naphthalimide Derivative and CPA Composite - Li, Lichao; Huang, Weiyun; Li, Liwei; Huang, Yan; Zhong, Anyong (Asian Journal of Chemistry, 2013)
In this study, to obtain more bulky molecules, change the conjugation length and reduce propensity of concentration quenching, 4-[2,4-di(tert-butyl)]phenoxy-N-(2-hydroxyethyl)-1,8- naphthalimide(1,8-naphthalimde derivative) was synthesized. An appropriate polymer as main chain was prepared as well. A series of polymer (N-CPA) with different ratio of 1,8-naphthalimide derivative were synthesized, N-CPA was investigated optically using photoluminescence spectroscopy. As the proportion of 1,8-naphthalimide derivative rose, the fluorescence quenching was advanced. Furthermore, the synthesized polymer was appropriate for forming thin film deposition from dilute polymer solution and the films were fully characterized by UV-visible spectroscopy and photoluminescence spectroscopy. The data of photoluminescence emission peaks, show pure blue photoluminescence both in solution and solid films with l PLmax locating at 445 nm around and relative narrow FWHM of 38-72 nm. But show red-shift in solid film compare to in solution.